Pengaruh Reputasi, Kualitas Informasi, dan e-WOM terhadap Minat Beli pada Situs Jual Beli Online Tokopedia yang Dimediasi oleh Kepercayaan Pelanggan - Dian Aisyah; Yunita Engriani (Jurnal Kajian Manajemen dan Wirausaha, 2019)
1) the influence of trust on buying interest in buying and selling sites a positive influence, (2) the influence of reputation on trust positive influence, (3) the influence of information quality on trust positive influence, (4) perception of e-WOM on trust positive influence, (5) the influence of reputation, quality of information, e-WOM influences buying interest through the belief of a positive influence, this type of research is causative research. This research was conducted in the city of Padang, West Sumatra. The population in this study are all Tokopedia site buying and selling sites but have never made a purchase. The sample used as many as 200 people using purposive sampling techniques. The type of data in this study is primary data. Data were collected through a questionnaire and analyzed using the SmartPLS version 3.0 program. (1) The tendency of trust has a positive and significant effect on buying interest, (2) The tendency of reputation has a positive and significant effect on trust, (3) the quality of information has a positive and significant effect on trust in a positive influence, (4) e-WOM uses a positive and significant effect on trust positive influence, (5) positive influence is positive and significant effect on the desire to buy, Keywords: Purchase Interest, Trust, Reputation, Information Quality, e-WOM